2007
DOI: 10.1007/s10508-007-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Social Embeddedness and Loneliness among Older Lesbian, Gay, and Bisexual Adults in the Netherlands

Abstract: Research has shown that aging lesbians, gay men, and bisexuals (LGBs) often experience feelings of loneliness. The main aim of this study was to examine whether older LGB adults in the Netherlands are lonelier than their heterosexual counterparts and, if so, whether the higher levels of loneliness can be attributed to a lower degree of social embeddedness. Using data from the Gay Autumn project and the NESTOR survey on Living Arrangements and Social Networks of Older Adults, we found that LGB elders were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 31 publications
4
63
2
Order By: Relevance
“…Broader social networks and supports were also investigated [32, 33, 46]. Social relationships and social networks were assessed for their presence, size, and impact.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Broader social networks and supports were also investigated [32, 33, 46]. Social relationships and social networks were assessed for their presence, size, and impact.…”
Section: Resultsmentioning
confidence: 99%
“…Having a partner and co-residing with that partner were associated with being White [49], younger [47, 59], and female [80]. Loneliness and social isolation, on the other hand, were associated with being male, being single, being less socially embedded, and having a smaller social network [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that women report more loneliness than men [6], while other studies report more loneliness among men [7]. Persons of minority groups have also been found to report increased loneliness [8,9]. These findings supported posits of the intersectional framework, which suggests that gender and race have an influence on loneliness.…”
Section: Introductionmentioning
confidence: 77%